Indigenous methodologies: characteristics, conversations and contexts - Kovach, Margaret (University of Toronto Press, 2009)
« An innovative and important contribution to Indigenous research approaches, this revised second edition provides a framework for conducting Indigenous methodologies, serving as an entry point to learn more broadly about Indigenous research" (résumé de l'éditeur). Divers chapitres s'intéressent à des dimensions relatives à la recherche partenariale, participative ou collaborative » [Résumé équipe ORPCC]
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; autochtones; orpcc; outils; pour des recherches en milieux de pratiques; périodes historiques; recherche en milieux de pratique; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions

Framework for Aboriginal-guided decolonizing research involving Métis and First Nations persons with diabetes - Bartlett, Judith G.; Iwasaki, Yoshitaka; Gottlieb, Benjamin; Hall, Darlene; Mannell, Roger (Social Science & Medicine, 2007)
« This paper documents the process of implementing an Aboriginal-guided research approach to examining the lived experiences of Metis and First Nations peoples with diabetes in Winnipeg, Manitoba, Canada. A newly developed Aboriginal-oriented process framework for decolonizing research includes, in order of application, the six processes of rationalizing, enabling, facilitating, experiencing, accepting, and enacting decolonizing research. We review the key methodological elements of our research as a basis for discussing this decolonizing process framework that challenges traditional western ways of doing research, and requires the reformulation of underlying assumptions and methods. Aboriginal-grounded decolonizing research processes have implications for health researchers and health service providers who work with Indigenous peoples worldwide and are particularly useful for developing culturally grounded, communitybased health promotion programs for Indigenous peoples suffering from health-related problems, including diabetes » [Résumé original]. On y trouve notamment un graphique sur des modalités de décolonisation des recherches, ainsi que plusieurs arguments réitérant l'importance de développer des pratiques de recherche culturellement adaptées [Résumé équipe ORPCC]
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; autochtones; décolonialisme; orpcc; outils; pour des recherches en milieux de pratiques; périodes historiques; recherche collaborative; recherche en milieux de pratique; recherche participative; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions